Stock market : random walk or mean reverting? - Sim, Gin Khai (Universiti Malaysia Sarawak (UNIMAS), 2011)
This study applies univariate as well as advanced unit root test for time series data to consider the Efficient Market Hypothesis (EMH) within eight (8) African stock markets. The stock prices data spanning from 1989:M7 till 2011:M3 is utilized for the stationarity tests. The results of the three conventional unit root tests show that the eight (8) African stock markets do not exhibit the mean reverting behavior. On the other hands, the results from the Lagrange Multiplier (LM) unit roots also show that all the tested African stock markets are consistent with EMH. Overall, all the tests have suggested the same verdict where all the tested African countries are under weak form efficiency. Hence, this study may suggest that all the tested African countries are ready to take up the obligation in leading other inefficient groups toward the financial integration within the Africa itself.